3x+2-6(x+1)=4x+2

Simple and best practice solution for 3x+2-6(x+1)=4x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+2-6(x+1)=4x+2 equation:


Simplifying
3x + 2 + -6(x + 1) = 4x + 2

Reorder the terms:
3x + 2 + -6(1 + x) = 4x + 2
3x + 2 + (1 * -6 + x * -6) = 4x + 2
3x + 2 + (-6 + -6x) = 4x + 2

Reorder the terms:
2 + -6 + 3x + -6x = 4x + 2

Combine like terms: 2 + -6 = -4
-4 + 3x + -6x = 4x + 2

Combine like terms: 3x + -6x = -3x
-4 + -3x = 4x + 2

Reorder the terms:
-4 + -3x = 2 + 4x

Solving
-4 + -3x = 2 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-4 + -3x + -4x = 2 + 4x + -4x

Combine like terms: -3x + -4x = -7x
-4 + -7x = 2 + 4x + -4x

Combine like terms: 4x + -4x = 0
-4 + -7x = 2 + 0
-4 + -7x = 2

Add '4' to each side of the equation.
-4 + 4 + -7x = 2 + 4

Combine like terms: -4 + 4 = 0
0 + -7x = 2 + 4
-7x = 2 + 4

Combine like terms: 2 + 4 = 6
-7x = 6

Divide each side by '-7'.
x = -0.8571428571

Simplifying
x = -0.8571428571

See similar equations:

| 8x^2-7x-20=0 | | -4(6w-1)=-2(2w+7) | | x-(-7x)=4+x | | 3-17x-14=9-15x-20 | | x^2+10x-y+28=0 | | 8x+-4-9x+17=180 | | -3x-5(-3x-9)=51 | | 7a+8b=24forb | | 10(1.666666667+0.3333333333y)-y=-2 | | 8x-4+9x+17=180 | | 3x-10+2x=10+X | | -570=5(8x-18) | | -3.5f=-21 | | Y=2Y+20 | | 9y+5x=14 | | 5-2(x+4)=7 | | 6x-(3x-5)=29 | | 3x-15-5x-23=90 | | 2(-1+0.5y)-y=-2 | | 4(x-6)=-3(x+2) | | Y=-3(5)+2 | | 3.4z-3.12=7.896 | | 2(6x+1)=4(5-x)-2 | | 26x-4+19x+4=180 | | y^2+7y+49=0 | | f(x)=(4x^2-25)(x^2+17x+72) | | -2w+19=-34 | | 7a+2x-13a+5ax-x= | | 30x=29x+4 | | 0.96y-.79=0.21y+0.45 | | y=180x-100000 | | g(2)=-2 |

Equations solver categories